Three-dimensional characterization of optical coherence tomography point spread functions with a nanoparticle-embedded phantom - Agrawal, Anant; Pfefer, T Joshua; Gilani, Naureen; Drezek, Rebekah (Optics letters, 2010)
We present a novel (to our knowledge) approach for measurement of the three-dimensional point spread function (PSF) of optical coherence tomography (OCT) systems using a nanoparticle-embedded phantom (NEP), toward development of standardized test methods for biophotonic imaging. The NEP comprises highly reflective plasmonic nanoparticles, homogeneously distributed in a transparent silicone matrix. OCT image volumes were analyzed to characterize PSFs in axial and lateral directions at a variety of locations in the NEP. Results indicate submicrometer agreement with conventional approaches to measure dimensions of the PSF. The NEP offers a robust approach for validating and comparing imaging performance of OCT devices.